2014
DOI: 10.1590/1414-431x20143527
|View full text |Cite
|
Sign up to set email alerts
|

Transduction motif analysis of gastric cancer based on a human signaling network

Abstract: To investigate signal regulation models of gastric cancer, databases and literature were used to construct the signaling network in humans. Topological characteristics of the network were analyzed by CytoScape. After marking gastric cancer-related genes extracted from the CancerResource, GeneRIF, and COSMIC databases, the FANMOD software was used for the mining of gastric cancer-related motifs in a network with three vertices. The significant motif difference method was adopted to identify significantly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Wu et al [13] investigated the response of cervical carcinoma to epidermal growth factor (EGF) using network motifs in the regulatory network. Other studies investigated signaling network-based biomarkers in breast cancer, [9,14,15] lung cancer, [16,17] gastric cancer, [18] and so on. [19,20] Large-scale sequencing investigations have revealed that signaling pathways initiate melanoma formation.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [13] investigated the response of cervical carcinoma to epidermal growth factor (EGF) using network motifs in the regulatory network. Other studies investigated signaling network-based biomarkers in breast cancer, [9,14,15] lung cancer, [16,17] gastric cancer, [18] and so on. [19,20] Large-scale sequencing investigations have revealed that signaling pathways initiate melanoma formation.…”
Section: Introductionmentioning
confidence: 99%